Character Formation through Islamic Religious Education: Integrating Role Modeling, Habituation, Contextual Learning, and Educational Technology in an Indonesian Madrasah - Sita Acetylena; Muhammad Zaironi (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
This study examines how character formation is implemented through Islamic Religious Education (PAI) by integrating role modeling, habituation, contextual learning, and educational technology in an Indonesian madrasah. Using a qualitative case study approach at MTs Al-Khoirot Malang, data were collected through classroom observations, interviews with teachers and school leaders, and documentation of learning activities. Data were analyzed thematically to identify patterns in character education practices. The findings reveal three main outcomes. First, an integrated character education model emerges, combining teacher role modeling, religious habituation, contextual learning, and technology use. Teachers exemplify ethical behavior, while routine practices such as congregational prayers and greeting culture reinforce moral consistency. Contextual learning links Islamic values to students’ daily lives, and digital media enhances engagement. Second, the study highlights the development of an Islamic moral school ecology, characterized by a supportive religious environment, respectful interactions, and collective worship that strengthen value internalization. Third, integrating contextual learning and technology increases student participation and deepens understanding of ethical teachings, positioning technology as a pedagogical reinforcement for character education.